2018
DOI: 10.1089/jayao.2018.0044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Utilizing the Unmet Needs of Teenagers and Young Adults with Cancer to Determine Priorities for Service Development: The Macmillan On Target Programme

Abstract: Areas identified for development included three specific initiatives applicable to other TYA services: a support website ( www.tyahelp.co.uk ); an electronic, age/developmentally specific, holistic needs assessment tool (the Integrated Assessment Map www.tyaiam.co.uk ); and a portal linking use of the IAM to resources within the Help website (video illustration available at: https://vimeo.com/191019826 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Existing referral policies were in line with those mandated by the specification for TYA cancer services set within NHS England. Time to diagnosis had been identified as a priority concern by patients involved in previous service development within the network [30].…”
Section: Methodsmentioning
confidence: 99%
“…Existing referral policies were in line with those mandated by the specification for TYA cancer services set within NHS England. Time to diagnosis had been identified as a priority concern by patients involved in previous service development within the network [30].…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study will add to the growing body of work in the needs of AYA oncology patients and support the tailoring of AYA-specific care. It also emphasizes the importance of patient experiences and needs in the development of age-specific health care services [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Survivors often expressed that needs around cognitive issues were unmet 33,34,51,54,60,61 . Jones et al 33 found that only 41% of survivors with cognitive concerns sought help and 47% of those experienced difficulty finding help.…”
Section: Unmet Information and Support Needsmentioning
confidence: 99%